Information-flow-based safety education (IFSE): an indispensable perspective on safety education - Gao, Kaixin; Zhou, Keping; Liang, Zhipeng (Journal of Civil Engineering and Management, 2021)
Any systems can be expressed by and connected with information. For the safety education system, doing so is essentially a process of safety information dissemination and cognition. Therefore, information is the core of the safety education system. At present, the key factors affecting the effectiveness of safety education are safety demand analysis information, the dissemination and cognitive processes of safety information and information feedback. Research on the construction of a framework model for safety education under the guidance of information flow clears and classifies information-related elements of the safety education process. Therefore, it is conducive to the construction of a safety education system to improve its management level and, through the rational use of information technology, to improve the conversion rate of safety information into safety behaviour. Based on a systematic review and comparison of the existing research perspectives on safety education and information-flow-based safety education (IFSE), this paper analyses the reasons why we need a new perspective on safety education. We introduce information flow into the safety education framework model. The fundamental and expanding elements of safety education propagation are examined and deduced based on information theory. Combined with the connotations of safety education and information flow, this paper analyses the implementation steps of IFSE and applies them to the safety education of new employees in metal and nonmetal mines. In the micro-design, virtual reality technology is used to integrate safety education content and information technology. A new perspective on safety education is created; then, the framework model of IFSE, its implementation steps and models of the processing and utilization processes of safety education are constructed. IFSE is a new perspective for realizing safety education in practice, and the framework model of IFSE provides rigorous theoretical knowledge. Of course, to improve IFSE in practice, more scientific and detailed evaluation methods need to be introduced. This paper is helpful for guiding the safety education theory research from “trivializes situated” to “systematic” and for guiding the design, implementation, assessment and optimization of the safety education practice.